Studies on Trypanosoma (Nannomonas) congolense. IExperimental immunization of mice against tsetse fly challenge - Nantulya, V.M.; Doyle, J.J.; Jenni, L. (Cambridge University Press, 1980)
Groups of mice were exposed to multiple bites by tsetse flies (Glossina morsitans morsitans) infected with a clone of Trypanosoma congolense spread over a period of 8 days. The mice were subsequently treated with Berenil 10 days after the first fly bite as were uninfected control mice. The group of mice which received 12–15 infectious fly bites on two occasions, 21 days apart, were subsequently resistant to infection when re-challenged by flies infected with the same clone of T. congolense. These mice were also immune to challenge by flies infected with a different bloodstream variable antigen type derived from this same stock. The immunity was stock-specific and directed against the metacyclic forms of the parasite, but was short-lived.